Mongol, Solongos, Nangiad "Mjangan üsgijn soël"-yn harʹcuulsan sudalgaa = Mong-gol, han-gug, jung-gug cheon-ja-mun bi-gyo-yeon-gu = Meng han han qian zi wen bi jiao yan jiu = Mongγol, Solungγus, Nangiyad "Mingγan üsüg-ün soyol"-un qaričaγuluγsan suduluγ-a - Sumʹjaabaatar, Baldandoržijn 1937-; Ch'oe, Ki-ho (Ulaanbaatar University Press, 2011)
Comparative Analysis of "The Thousand Character Classic" in Chinese, Korean and Mongolian